Ethical issues of electronic advertising and their impact on the Iraqi consumer (A field study of the public in Baghdad - Arsan, Prof .Dr.Arsan Yousif; Hashem, Rand saad (Thi Qar Arts Journal, 2024)
This research aims to identify the reality of electronic advertising from the ethical perspective, through the research problem represented by the main question (What are the ethical issues of electronic advertising and their repercussions on the Iraqi consumer?), as this research is considered a descriptive study, and I used the survey method, using the questionnaire tool, For the research sample, which numbered (400) male and female respondents, it included males with a frequency of (182) and 45.5% of female respondents, with a frequency of (218) and 54.5% of female respondents. Perhaps the most important results that the researcher reached are the following: that electronic advertisements were not approved On the principle of honesty and did not avoid deceiving the public, and this contradicts the ethics of electronic advertising, the results showed that electronic advertisements on social networking sites She did not adhere to social values ​​and customs, and this is a very dangerous moral indicator